Suicide means, timing, intent and behavior characteristics of the suicides with schizophrenia. (December 2021) - Lyu, Juncheng; Zhang, Jie
Highlights: Suicide Means, Timing, intent and behavior characteristics of the suicides with schizophrenia. The study is based on one of the largest psychological autopsy studies in China with 392 suicides and 416 community controls. Chinese version of the SCID was used to estimate the mental illnesses both in the suicide cases and controls. Characteristics of the suicides with diagnosed schizophrenia were studied in comparison with other suicides in the sample. Schizophrenic suicide was more likely to happen in the second quarter of the year (April – June), middle of the month (11th-20th), and in the afternoon (3:00pm – 6:00pm). The schizophrenic suicides had higher suicide intent than those without schizophrenia and were more inclined to be isolated, more likely to tell people their suicide intent, and less likely to prepare posthumous papers. Abstract: Background: Studies have been reported on suicide and schizophrenic suicide, but few compared certain characteristics of suicides with and without schizophrenia. Methods: A sample of 392 suicides was consecutively recruited from 16 counties in three provinces of China. Psychological autopsy method was applied to collect the information through informants. The questionnaire of characteristics for suicidal behavior, Beck's Suicide Intent Scale (SIS), and the DSM-IV based SCID were applied. Results: About 9.7% of the sampled suicides ( n = 38) were diagnosed with schizophrenia, and they were more likely to be female and older in age. No significant differences were found on violent suicide means, but significant differences within non-violent means between two groups. Schizophrenic suicide was more likely to happen in the second quarter of the year (April – June), middle of the month (11th-20th), and in the afternoon (3:01 pm – 6:00 pm). The schizophrenic suicides had higher suicide intent than those without schizophrenia and were more inclined to be isolated, more likely to tell people their suicide intent, and less likely to prepare posthumous papers. Conclusion: Schizophrenic suicides have unique characteristics, and targeted preventive measures should be taken to prevent schizophrenic suicides. To accurately identify characteristics of suicide behavior is meaningful to prevent schizophrenic suicides in clinical practice.